Radon monitoring in the Harmanecká Cave, Slovakia - Smetanová, Iveta; Pristašová, Lucia; Haviarová, Dagmar; Csicsay, Kristian (Contributions to Geophysics and Geodesy, 2026)
Radon survey in the Harmanecká Cave was conducted from December 2023 to November 2024 using Ramarn track detectors placed in 8 stations inside the cave and one station in the cavity developed in the same karst system outside the cave. Detectors were changed every three months. Annual average of radon activity concentration inside the cave varied between 930 and 2240 Bq/m3, in the cavity it was equal to 222.5 Bq/m3. Seasonal variation was observed at all sites, and its different character among sites was proven. A possible relation between radon and microclimate and meteorological parameters was investigated, but no clear relationship was observed. Assessing their possible effect on radon using three-month data is therefore not appropriate and continuous measurements are needed. Estimated annual effective dose for the cave guides was below the limit of 20 mSv.